ANALISIS KOMPOSISI TUMBUHAN DAN KETERHIDUPAN MINIMUM DI TAMAN WISATA ALAM PULAU KEMBANG KECAMATAN ALALAK KABUPATEN BARITO KUALA PROVINSI KALIMANTAN SELATAN - Hermawan Hermawan; Gusti Syeransyah Rudy; Ahmad Yamani (Universitas Lambung Mangkurat, 2023)
Research on Plant Composition Analysis and Minimum Livelihood in Pulau Kembang Island Natural Park, Alalak District, Barito Kuala Regency, South Kalimantan Province was carried out on Pulau Kembang, Alalak District, Barito Kuala Regency, South Kalimantan Province. With the aims of analyzing the composition of plant species and Minimum Livelihood. The method used is a tiled line, to record all growth rates ranging from the level of seedlings, stakes, poles and trees. The results of the study analyzed the dominant type of vegetation at the seedling level, namely fires (Avicennia officinalis L.) with an Important Value Index (INP) of (71.63%), and rambai (Baccaurea motleyana) with an Important Value Index (INP) of (51.08%). From the results of the analysis of vegetation species that dominate at the stake level, namely Api-Api (Avicennia officinalis L.) with an Important Value Index (INP) of (37.12%), and rambai (Baccaurea motleyana) with an Important Value Index (INP) of (35.86%). From the results of the analysis of vegetation, the types that dominate at the pole level are Buta-Buta (Exocoecaria Agallaoca) with an Important Value Index (INP) of (43.02%), and rambai (Baccaurea Motleyana) with an Important Value Index (INP) of (41.42%). Based on the results of the analysis of vegetation species that dominate at the tree level, namely pulantan (Alstonia sp) with an Important Value Index (INP) of (66.67%), and rengas (Gluta Renghas) with an Important Value Index (INP) of (62.50%). The Minimum Livelihood Value (NKM) of all types found in this study exceeded 0.1 so that the condition of the plants at the study site was still preservedPenelitian Analisis Komposisi Tumbuhan Dan Keterhidupan Minimum Di Hutan Wisata Pulau Kembang Kecamatan Alalak, Kabupaten Barito Kuala, Provinsi Kalimantan dilaksanakan di Pulau Kembang Kecamatan Alalak Kabupaten Barito Kuala, Provinsi Kalimantan Selatan. Dengan tujuan untuk menganalisis komposisi jenis tumbuhan dan Keterhidupan Minimum. Metode yang digunakan adalah garis berpetak, untuk merekam semua tingkat pertumbuhan mulai dari tingkat semai, pancang, tiang dan pohon. Hasil penelitian analisis vegetasi jenis yang mendominasi pada tingkat semai yaitu api-api (Avicennia officinalis L.) dengan Indeks Nilai Penting (INP) sebesar (71,63%), dan rambai (Baccaurea Motleyana) dengan Indeks Nilai Penting (INP) sebesar (51,08%). Dari hasil analisis vegetasi jenis yang mendominasi pada tingkat pancang yaitu api-api (Avicennia officinalis L.) dengan Indeks Nilai Penting (INP) sebesar (37,12%), dan rambai (Baccaurea Motleyana) dengan Indeks Nilai Penting (INP) sebesar (35,86%). Dari hasil analisis vegetasi jenis yang mendominasi pada tingkat tiang yaitu buta-buta (Exocoecaria Agallaoca) dengan Indeks Nilai Penting (INP) sebesar (43,02%), dan rambai (Baccaurea Motleyana) dengan Indeks Nilai Penting (INP) sebesar (41,42%). Dari hasil analisis vegetasi jenis yang mendominasi pada tingkat pohon yaitu pulantan (Alstonia sp) dengan Indeks Nilai Penting (INP) sebesar (66,67%), dan rengas (Gluta Renghas) dengan Indeks Nilai Penting (INP) sebesar (62,50%). Nilai Keterhidupan Minimum (NKM) dari semua jenis yang ditemukan dalam penelitian ini melebihi dari 0.1 sehingga keadaan tumbuhan di lokasi penelitian tersebut masih terjaga kelestariannya